Out Of The Shadows: On Writing Shadows Under the Poplar Tree - Áróra Einarsdóttir 1991- (2016)
The following thesis is the result of two courses the writer attended at the University of Iceland: a Shakespeare class taught by Dr. Martin Regal in the fall of 2015 and a Creative Writing class taught by Dr. Anna Heiða Pálsdóttir in the spring of 2015. It consists of a historical novella, Shadows Under the Poplar Tree, which was inspired by the play Measure for Measure by Shakespeare, and a report on the writing process. The novella is roughly 30,000 words and the report is just under 5,000 words. The setting is Vienna in the 1600s. A man is condemned to death. His crime? He has conceived a child out of wedlock. His sister is about to take her vows to a nunnery but upon hearing of her brother’s sentencing she rushes to his aid. The only way the judge will relent is if she agrees to spend the night with him. Outside the city walls in a crumbling and decaying house dwells another woman wronged by the judge. Alone in her despair, she has spent five years hating him. The two women are brought together by a mysterious, faceless monk. At first, their only attraction to each other is the mutual desire for revenge upon the judge but as they become closer, something more tender and loving blossoms between them. Will their newfound love survive their desire for revenge? Who is the hooded monk lurking in the shadows? In the exposition Out of the Shadows I discuss my inspiration for the novella, the detailed research I undertook into Vienna of the 1600s, Elizabethan fashion, housing, and religion. I share my thoughts on the writing process and what advice from writers and other professionals on structuring plot and writing dialogue I found most helpful.